ANALISIS PENGARUH BID-ASK SPREAD, MARKET VALUE DAN VARIANCE RETURN TERHADAP HOLDING PERIOD SAHAM SEKTOR PERTAMBANGAN - Novita Selvia Perangin-angin; Fauzie Syarief (Departemen Ekonomi Pembangunan USU, 2013)
ABSTRACT The formulation of the problem is to know the influence of bid-ask spread, market value and variance return on stock holding period in mining sector. The objective of this research to analyze the influence of bid-ask spread, market value and variance return on stock holding period in mining sector. The data used were 10 companies selected using purposive sampling technique with the criteria (1) The companies in mining sector registered in Jakarta Exchange. (2) The companies which were actively consistent during in the period 2009 up to 2011 in Jakarta Exchange. (3) The companies fulfilling the indicator of dependent and independent variables during in the period 2009 up to 2011. The data to analyze in this research were panel data using Multiple Linier Regression with Fixed Effect Model (FEM) in accordance with this model having the intercept equation and it was not constant or with difference on every individual. Before analyzing the data, it was tested firstly with Normality test and Hausman test to know the normality of data and to know which method is appropriate with fixed effect model in this research. Further, data processing was done using Eviews 7 program.The results of research showed that simultaneously through f-statistic test the variable of bid-ask spread, market value and variance return had significant influence to stock holding period in mining sector on significance rate 95%,whereas based on t-statistic test, it can be concluded that the variable of bid-ask spread and market value had positive influence and insignificant influence to stock holding period in mining sector and variance return with negative significant to stock holding period of mining sector in period of 2009 up to 2011 with significance rate 95%. In addition, the coefficient of determination showed that the variable of bid-ask spread, market value, and variance return are capable only to explain that the variable of stock holding period in mining sector for 65.15%. Keywords: Stock Holding Period, Bid-Ask Spread, Market Value and Variance Return.